Psychometric Properties of the Elementary Social Behavior Assessment in Swedish Primary School: A Teacher Rated Index of Students’ Prosocial School Behaviors - Wikman, Carina; Allodi, Mara Westling; Ferrer-Wreder, Laura (Frontiers in Education, 2021)
The aim of this study was to examine the psychometric properties of a Swedish language adaption of the teacher-rated Elementary Social Behavior Assessment (ESBA), which provides an index of social skills. Participants were eight teachers (two teachers per school in four schools) who rated their second-grade students (N = 143 child ratings, M age = 8 years old). The ESBA factor structure was tested with Confirmatory Factor Analysis in a series of one, two, and three-factor models. The two- and three-factor models showed good fit. ESBA showed high internal consistency at the observed scale level. The ESBA psychometric properties in show initial promise as a tool that could help Swedish teachers to identify and support student social skills development.